ALDH2C4 regulates cuticle thickness and reduces water loss to promote drought tolerance. (October 2022) - Liu, Li-Li; Deng, Yun-Quan; Dong, Xin-Xiu; Wang, Cheng-Feng; Yuan, Fang; Han, Guo-Liang; Wang, Bao-Shan
Abstract: In Arabidopsis thaliana, ALDH2C4 encodes coniferaldehyde dehydrogenase, which oxidizes coniferaldehyde to ferulic acid. Drought stress is one of the important abiotic stresses affecting plant growth. However, the role of ferulic acid in drought resistance is unknown. To investigate the contribution of ferulic acid to cuticle composition and drought resistance, we used two Arabidopsis aldh2c4 mutant lines. Compared with wild-type (WT) leaves, ferulic acid contents were significantly lower (by more than 50 %) in mutants. The mutants also had lower amounts of cutin and wax, primarily due to reductions in C18:2 dioic acid and alkanes, respectively. Furthermore, the leaves of the mutant plants exhibited greater rates of water loss and released chlorophyll faster than WT leaves when immersed in 80 % ethanol, indicating a defective cuticle barrier. The growth of aldh2c4 mutants was severely inhibited, and their leaves showed a higher degree of wilting relative to the WT plants under drought conditions. In aldh2c4 complementation lines, the growth inhibition of the mutant plants under drought stress was alleviated. Taken together, our results demonstrate that ferulic acid plays an important role in the composition and structural properties of the cuticle and that a ferulic acid deficiency in the cutin leads to reduced drought tolerance. Highlights: In aldh2c4, the contents of C18:2 dioic acid in the cutin, and C29 and C31 alkanes in the wax were significantly decreased. The epidermal permeability of rosette leaves was significantly increased in aldh2c4 mutants. ALDH2C4 significantly improves the drought resistance of plants.